Sustainable Supply Chain Management Practices for Environmental and Social Integrity - Ali, Bashar Mahmood; Majeed, Majed Abdullah; Latif, Nabaa; Aldrickzler, Rasha (Journal of Ecohumanism, 2024)
Background: Research on sustainable supply chain management (SSCM) is essential as the need to balance economic growth with environmental conservation and social responsibility becomes increasingly urgent. Traditional supply chain practices often overlook these factors, leading to significant environmental damage and societal inequalities. Objective: This study aims to examine and assess sustainable supply chain management practices that enhance environmental and social responsibility. This research aims to offer organizations a detailed framework for successfully implementing sustainable strategies by recognizing important practices and evaluating their effects. Methods: A mixed-methods approach was used, integrating a thorough literature review with examinations of case studies from top companies in different sectors. Industry reports and sustainability performance metrics provided quantitative data, while interviews with supply chain managers and sustainability experts yielded qualitative insights. Results: The results suggest that implementing SSCM strategies like eco-friendly purchasing, circular supply chains, and involving stakeholders can greatly improve environmental and social results. Businesses who implemented these strategies saw a 30% drop in carbon emissions, a 25% boost in resource efficiency, and a 20% enhancement in labor conditions. Furthermore, 85% of companies that were surveyed reported improved community relations and higher levels of customer satisfaction. Conclusion: The study concludes that sustainable supply chain management practices are social integrity can only be attained through the implementation of sustainable supply chain management practices. Organizations that actively incorporate these practices not only help to achieve sustainability objectives but also benefit from competitive advantages by improving their reputation and operational efficiency. The study emphasizes the importance of ongoing innovation and teamwork in promoting SSCM and suggests implementing policy measures to encourage extensive use.